Christmas Mass Movements in the Italian Alps - Marta Chiarle; Costanza Morino; Giovanni Mortara; Walter Alberto; Mario Ravello; Aristide Franchino; Giuseppe Orombelli; Marco Giardino; Luigi Perotti; Guido Nigrelli (Revue de Géographie Alpine)
Mass movements at high elevation during wintertime are rare events in the Italian Alps, but are generally large events compared to those occurring in other seasons. In a context of climate change, their interpretation is particularly challenging due to the risk implications during a highly tourist season in the mountains, and because their occurrence seemingly contradicts the attribution of recent mass movements in high-alpine environments to global warming. To shed some light on this topic, we reviewed 12 mass movements in the Italian Alps that occurred at elevations above 1500 m, documented from mid-December to January, henceforth during the Christmas period. The aim is to understand whether recent events may be related to ongoing climate and environmental changes. Even though the small number of analysed mass movements does not allow statistically based conclusions, some preliminary considerations could be drafted. We observe a seeming increase in the frequency and elevation of winter mass-movement events in the last two decades, with an increased number of failures involving rock slopes under permafrost conditions, and a transition from heavy-precipitations controlled mass movements to temperature-anomalies and -fluctuations controlled mass movements. We also show that any type of instability process can occur in winter, including debris flows, with rock falls/avalanches prevailing. These findings may partly stem from an increased number of mass-movement reports deriving from the growing attention in recent years to the impacts of climate change and their related risks. Considering the growing anthropic pressure on alpine areas even in winter, especially for tourism purposes, it is crucial to broaden our knowledge on winter mass movements by expanding and analysing a larger case history, through the opportunities offered by new technologies and citizen science.